2019
DOI: 10.2169/internalmedicine.1698-18
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatemic Osteomalacia Associated with Adefovir-induced Fanconi Syndrome Initially Diagnosed as Diabetic Kidney Disease and Vitamin D Deficiency

Abstract: A 68-year-old man with type 2 diabetes mellitus and chronic hepatitis B infection was referred to the nephrology department before planned surgery for hepatocellular carcinoma. He had been receiving low-dose adefovir dipivoxil (ADV) for 11 years. Laboratory findings revealed impaired re-absorption in the proximal renal tubules. He had been diagnosed with diabetic kidney disease and osteomalacia due to vitamin D deficiency; thus, ADV was not discontinued until he was referred to us. In this case, concomitant di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…A case of TIO due to meningioma and effective burosumab treatment was published recently [28]. Moreover, several drugs such as adefovir or intravenous iron therapy can lead to hypophosphatemia and similar symptoms to XLH [29,30]. Therefore, TIO, drug-induced hypophosphatemia and other forms of osteomalacia and renal tubular phosphate wasting must also be considered in adult patients with low phosphate levels.…”
Section: Differential Diagnosis Of Low Phosphate Levels In Adultsmentioning
confidence: 99%
“…A case of TIO due to meningioma and effective burosumab treatment was published recently [28]. Moreover, several drugs such as adefovir or intravenous iron therapy can lead to hypophosphatemia and similar symptoms to XLH [29,30]. Therefore, TIO, drug-induced hypophosphatemia and other forms of osteomalacia and renal tubular phosphate wasting must also be considered in adult patients with low phosphate levels.…”
Section: Differential Diagnosis Of Low Phosphate Levels In Adultsmentioning
confidence: 99%
“…However, several recent studies reported low FGF23 levels in patients with ADV-induced FS, suggesting the FGF23 may not cause hypophosphatemia in patients with drug-induced FS 33 and it may not be involved in the development of HO induced by ADV. 34…”
Section: Genetic Predisposition Characteristicsmentioning
confidence: 99%
“…The main characteristics of 32 patients with ADV-induced FS, including eight patients in our institution and 24 published cases, are summarized in Table 4 . 5 , 18 , 22 , 23 , 36 43 …”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation